Plant-derived mitochondria-targeting cysteine-rich peptide modulates cellular bioenergetics - Kam, Antony (2019)
Mitochondria are attractive therapeutic targets for developing agents to delay age-related frailty and diseases. However, few promising leads have been identified from natural products. Previously, we identified roseltide rT1, a hyperstable 27-residue cysteine-rich peptide from Hibiscus sabdariffa, as a knottintype neutrophil elastase inhibitor. Here, we show that roseltide rT1 is also a cell-penetrating, mitochondria-targeting peptide that increases ATP production. Results from flow cytometry, live-cell imaging, pulldown assays, and genetically-modified cell lines supported that roseltide rT1 enters cells via glycosaminoglycan- dependent endocytosis, and enters the mitochondria through TOM20, a mitochondrial protein import receptor. We further showed that roseltide rT1 increases cellular ATP production via mitochondrial membrane hyperpolarization. Using biotinylated roseltide rT1 for target identification and proteomic analysis, we showed that human mitochondrial membrane ATP synthase subunit O is an intramitochondrial target. Collectively, these data support our discovery that roseltide rT1 is a first-in-class mitochondria-targeting, cysteine-rich peptide with potentials to be developed into tools to further our understanding of mitochrondria-related diseases.